Edukasi Pencegahan Stroke pada Masyarakat Desa Cigugur Girang: Stroke Prevention Education in Cigugur Girang Village - Goenawan, Hanna; Tarawan, Vita Murniati; Radhiyanti, Putri Teesa; Ramadhanti, Julia; Lesmana, Ronny (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Stroke patients could get sequelae, and it will decrease the patient’s quality of life. Stroke could be caused by comorbid diseases such as hypertension, diabetes mellitus, and dyslipidemia. Thus, stroke could be prevented by reducing the comorbid diseases. The prevention of stroke is necessary to be done in order to reduce stroke cases, especially in Bandung’s rural area. Villagers have limited access to health information and health services. In this community service, the methods we used were to screen the two risk factors of stroke (blood pressure and blood glucose ad random measurement) in Cigugur Girang Village, West Bandung area. The aim of this community service is to find comorbid factors of stroke and give education to people who have one or more stroke risk factors. The results of the blood pressure measurement screening showed that more than 40% of the residents of Cigugur Girang village had blood pressure above normal, and 5% of the population had blood sugar levels higher than normal. The risk factor for stroke in residents of Cigugur Girang Village mainly is high blood pressure. In this community service, people with high blood pressure were educated on how to maintain normal blood pressure and how to change their lifestyle. On the other hand, some participant has high blood glucose level. High blood glucose levels will develop into diabetes mellitus. In this education program, we gave information about the complications of high blood glucose, including stroke. Thus, this education program could increase community awareness to prevent stroke.